PENGEMBANGAN MEDIA BOARD GAME “PROYEK GALAKSI BIMASAKTI” UNTUK MENINGKATKAN HASIL BELAJAR - Arianti, Ratiwi; Fitriyah, Isnanik Juni; Puji, Amelia Dwi; Firmansyah, Mohammad Rifan (EduFisika: Jurnal Pendidikan Fisika, 2024)
This study aimed to determine the effect of developing the media board game "Galaksi Bimasakti Project," which is the development of the Snakes and Ladders game. The Galaksi Bimasakti Project has a colorful space design that makes it attractive to students. This game is equipped with pawns, dice, and 3 types of cards: question cards, answer confirmation cards, and punishment cards. The novelty of the Snakes and Ladders concept game is that question cards and answer confirmations have the same number, making it easier for students to find out whether the answers put forward by other players are right or wrong. Other participants will listen and remember the appropriate answers, besides that the attractive design and additional points make students more interested in answering correctly and contributing to their group. In this game the teacher is only a supervisor of the course of the game, in other words the teacher is only a facilitator. The game is carried out by peer tutors in groups so that in preparation for the game. The method used in data analysis is descriptive quantitative using a group design pretest-post-test. The results showed that there was an increase in the class average at the pretest and post-test. Obtained statistical test results of 0.000 stated that there was an influence of the media on learning outcomes after the implementation of the Galaksi Bimasaktit board game.